Tombs of the South Asasif Necropolis : Thebes, Karakhamun (TT 223), and Karabasken (TT 391) in the Twenty-Fifth Dynasty - Pischikova, Elena; Pischikova, Elena (American University in Cairo Press, 2014)
This volume is a joint publication of the members of the American-Egyptian mission South Asasif Conservation Project, working under the auspices of the State Ministry for Antiquities and Supreme Council of Antiquities, and directed by the editor. The Project is dedicated to the clearing, restoration, and reconstruction of the tombs of Karabasken (TT 391) and Karakhamun (TT 223) of the Twenty-fifth Dynasty, and the tomb of Irtieru (TT 390) of the Twenty-sixth Dynasty, on the West Bank of Luxor